KAJIAN STRUKTURAL PADA PUISI “KEKASIHKU” KARYA JOKO PINURBO - Neng Tuti Novianty (Populer: Jurnal Penelitian Mahasiswa, 2022)
This article discusses the structural study of the poetry “Kekasihku” by Joko Pinurbo. The focus of the discussion of this article is to describe the physical structure and inner structure of the poetry which is carefully described in the form of words, sentences and discourse. This research method is descriptive qualitative using a structural approach. The data source used as the object of research is one of the poetry contained in the book collection of poetry "Kekasihku" by Joko Pinurbo, published in 2004. The results and discussion in this article contain ( 1) the physical structure of poetry includes: (a) diction, (b) images, (c) figure of speech, (d) concrete words, (e) rhyme/rhythm, and (f) typography. The dominant physical structure is simple diction by creating communicative activities and not eliminating the aesthetic value of poetry. (2) The inner structure of poetry includes: (a) theme, (b) tone, (c) taste, (e) message. The element that dominates the inner structure of poetry is the feeling that creates inner experiences through writing.